2014
DOI: 10.1158/1078-0432.ccr-13-2761
|View full text |Cite
|
Sign up to set email alerts
|

Expression Signature Defined byFOXM1–CCNB1Activation Predicts Disease Recurrence in Non–Muscle-Invasive Bladder Cancer

Abstract: Purpose: Although standard treatment with transurethral resection and intravesical therapy (IVT) is known to be effective to address the clinical behavior of non–muscle-invasive bladder cancer (NMIBC), many patients fail to respond to the treatment and frequently experience disease recurrence. Here, we aim to identify a prognostic molecular signature that predicts the NMIBC heterogeneity and response to IVT. Experimental Design: We analyzed the genomic profiles of 102 patients with NMIBC to iden… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 34 publications
1
58
0
Order By: Relevance
“…Our data revealed that the increased activity and expression of FOXM1 in NMIBC identifies primary tumors at high risk of recurrence, and the possibility that these tumors display invasive characteristics in the recurrences. These data support the previous FOXM1dependent gene signature related to recurrence in bladder cancer (54). Moreover, integrative global genomic analyses of advanced bladder cancer supported its relevance (10,11).…”
Section: Discussionsupporting
confidence: 87%
“…Our data revealed that the increased activity and expression of FOXM1 in NMIBC identifies primary tumors at high risk of recurrence, and the possibility that these tumors display invasive characteristics in the recurrences. These data support the previous FOXM1dependent gene signature related to recurrence in bladder cancer (54). Moreover, integrative global genomic analyses of advanced bladder cancer supported its relevance (10,11).…”
Section: Discussionsupporting
confidence: 87%
“…In our study, IL8 is the second highest enriched connectivity nodes. Surprising, further investigation indicates that IL-8-stimulated cell proliferation correlates with alteration of cell cycle distribution by increasing levels of cell cycle-regulated Cyclin D1 and Cyclin B1 proteins as well as activation of PI3K/Akt and Raf/MEK/ERK [34]. Therefore, IL8 and CCNB1 may have potential function in the progress of bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As a member of an evolutionarily conserved family of transcription factors characterized by a DNA-binding domain called the Forkhead Box (Kalin et al, 2011), FOXM1 is also known as a representative proliferationassociated transcription factor, such as prostate cancer (Lokody, 2014), hepatocellular carcinoma (Yamashita et al, 2014), glioblastoma (Gong et al, 2015), and bladder cancer (Kim et al, 2014). The overexpression of FOXM1 observed that FOXM1 is associated with an aggressive phenotype and poor prognosis in patients with breast cancer (Rajamanickam et al, 2016).…”
Section: Discussionmentioning
confidence: 99%